The Currency Composition of Foreign Exchange Reserves : Retrospect and Prospect - Eichengreen, Barry; Mathieson, Donald (Washington, D.C. : International Monetary Fund, 2000)
This paper examines the determinants of the currency composition of international reserves. Our single most important finding is the striking stability over time of the relationship between the demand for reserves denominated in different currencies and its principal determinants: trade flows, financial flows and currency pegs. This result contrasts sharply with recent predictions of sharp shifts in the currency composition of central banks' holdings of foreign exchange. The message would seem to be that in this, as in other respects, the international monetary system is in a mode of gradual, continuous evolution, not of rapid, discontinuous change.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet